Reliability of the Indiana Supplemental Nutrition Assistance Program-Education (SNAP-Ed) Program Evaluation Survey (P04-074-19) - Rivera, Rebecca (Curr Dev Nutr, 2019)
OBJECTIVES: Supplemental Nutrition Assistance Program-Education (SNAP-Ed) is a national program that delivers nutrition education to low-income households to improve nutrition-related behaviors. A pre-post survey, or Medium Term Survey (MTS), is used to determine participant behavior change as a result of the program. The objective of the present study was to determine the short-term (4–10 weeks) and long-term (1 year) reliability of the Indiana SNAP-Ed MTS. METHODS: Data for this secondary analysis was from a randomized controlled trial evaluation of Indiana SNAP-Ed. SNAP-Ed-eligible adults (≥18 yrs) living in Indiana and interested in receiving nutrition education were recruited from 2015–2016 (N = 261). Short-term and long-term test-retest reliability of the 17 pre- and post-test items on the Indiana SNAP-Ed MTS were determined using Spearman correlations. MTS pre-test results from the control group who did not receive SNAP-Ed were compared with post-test results collected 4–10 weeks (short-term) later and 1 year (long-term) later, respectively. Analyses were completed using SAS 9.4. Significance was P ≤ 0.05. RESULTS: The Indiana SNAP-Ed MTS demonstrated poor test-retest reliability with correlation coefficients of 0.4 to 0.6 for 15 items over the short-term (P < 0.05) and correlation coefficients of 0.3 to 0.7 for 11 items over the long-term study period (P < 0.05) among Indiana SNAP-Ed-eligible adults who did not receive the SNAP-Ed intervention (n = 62). CONCLUSIONS: Among Indiana SNAP-Ed-eligible adults, the Indiana SNAP-Ed MTS is not a reliable survey instrument to assess nutrition-related behaviors over a short-term or long-term time period. Further research is needed to develop reliable survey items to conduct program evaluation. FUNDING SOURCES: This activity was funded by the Purdue Office of Undergraduate Research Scholarship, the Purdue Nutrition Education Program, and a USDA NIFA Hatch Project.